Open space. An asset without a champion? - (:unkn) unknown (My University, 2011)
Governments have long recognised the need to preserve certain open space lands because of their importance, but Open Space: an asset without a champion? reveals the new impetus for open space creation and preservation is coming from the private sector. With both public and private players universally recognising the value of open space, it is no surprise that collaboration is the number one item on the open space agenda.
Keywords: Freifläche; Freiraum; Freiraumplanung; Stadtökologie; Öffentliche Grünfläche; Lebensraum; Lebensqualität; Public-Private-Partnership